The North European Pipeline: Increasing energy security or political pressure? - Roland Götz (Stiftung Wissenschaft und Politik (SWP), 2005)
On 8 September 2005, German and Russian industry, in the presence of both Chancellor Gerhard Schröder and President Vladimir Putin, signed an agreement on the construction of the much-discussed natural gas pipeline running offshore through the Baltic Sea. The Russian monopolist Gazprom has been intensely interested in this pipeline over the past years, as it would create an alternative gas transport route to Western Europe, which has traditionally led through Belarus, Ukraine, and Poland. However, while a key selling point for this deal, German energy security will, in fact, not be increased by the pipeline, - especially, if compared to its alternative, the expansion of existing continental pipelines. The traditional transit countries have expressed concern over the German-Russian move, since they fear that their interests have not been taken into account. These concerns could be addressed by including transit countries into the German-Russian Energy Dialogue. (SWP-Comments / SWP)
Keywords: 320